An ecosystem view on third party mobile payment providers: a case study of Alipay wallet. Issue 5 (8th August 2016) - Guo, Jie; Bouwman, Harry
Abstract : Purpose: To understand why the penetration of handset-based mobile payment in most countries is still low has been an important research topic for the last 15 years, and it has been analyzed from different perspectives. However, the analysis of a single aspect cannot provide a sophisticated answer to the complicated underlying question. The purpose of this paper is to understand how a relatively successful m-payment ecosystem is created and sustained through the coopetition of various actors. Design/methodology/approach: To that end, the authors analyze the case of Alipay wallet, the m-payment service provider with the largest market share in China, and focus on understanding the motivations and subsequent actions of the organizations cooperating in the Alipay wallet core ecosystem. Findings: The results show that actors with heterogeneous and complementary resources can forge sustainable collaboration. Within an ecosystem, although always constrained by resources and capabilities, the actions that the core actors take and the resulting power imbalances are dynamically changing, reflecting actors' aim of reducing uncertainty. Research limitations/implications: The main limitation of this case is that it was conducted in a Chinese context, which has specific features that may not apply to other cases. In addition, this study is based on a single case study in a single country, without comparing the results to any other cases or countries. Therefore, some modifications may have to be made when applying the framework and generalizing the results. Practical implications: With regards to the practical perspective, the Alipay case may serve as an example that other providers follow, taking similar actions to increase the dependency of others and reduce their own dependency on others. It is helpful to take a keystone strategy to create value within the ecosystem and share this value with other participants. Moreover, Alipay acts as the platform provider, in addition to managing value creation within the ecosystem and sharing that value with the other participants. Alipay focuses on the business and strategic needs of the core actors, without threatening their main business, for example, Alipay focuses on micro-payments, which does not pose a direct competition to banks, who mainly rely on macro-payments to generate profit. Micro-payments are often related to high transaction costs for banks. In addition, although it is difficult to define the boundaries of actors in the ecosystem, the core business of every actor is the key competitive or even survival condition. This notion should be taken into consideration by actors whose actions affect the business of other ecosystem partners. For instance, Alipay will not aim to become a bank, as they know that if they do so, they cannot connect any other bank to their platform. In other words, the scope and boundary of the actors are clearly identified so that the core business will not be threatened. Sords, we can learn from Alipay that it pays off to focus on one area, and not to let your competitors challenge you. Originality/value: The authors proposed the StReS framework for analyzing a business ecosystem by combining resource-based review, resource dependency theories and network analysis for investigating the motivations of the organizations cooperating in the core ecosystem and the actions they have taken to reduce dependency and uncertainty.